Commuter complaints on SMRT train breakdowns - VARGHESE, Susheela A. (Institutional Knowledge at Singapore Management University, 2013)
In December 2011, the world renowned SMRT train system in Singapore suffered a series of commuter disruptions that shattered public confidence in the system. SMRT Corporation Ltd. is Singapore’s multi-modal public transport operator, with train, bus and taxi services across the island. This case recounts the train breakdowns, resulting commuter frustration and SMRT’s responses. Not only does SMRT management need to restore confidence in the reliability and safety of the system, but also they need to restore good faith with the public that they are committed stewards of a public system integral to daily living. This influence case examines credibility as the major requirement for organisational reputation, examining how different stakeholders define credibility and resulting reputation according to their needs. An important aspect of maintaining reputation can be alertness to trends that develop from various events in the external environment. Such trends sometimes erupt into issues in the face of a crisis. The case illustrates how early issues management and effective crisis management require both actions and communications as good-faith repair strategies.